Neuromodulation and memory: exploring ethical ramifications in memory modification treatment via implantable neurotechnologies - Claudia González-Márquez (Frontiers in Psychology, 2023)
Invasive implantable neurotechnologies capable of simultaneously altering and recording neural activity are no longer the exclusive province of science fiction but a looming reality that will revolutionize medical practice. These advancements, particularly in their memory-altering capabilities, herald a vast array of opportunities for addressing the complex landscape of neurodegenerative and psychiatric conditions linked to memory impairments. However, the panoply of ethical implications arising from such a novel neurotechnology remains relatively unexplored by the neuroethics literature. This study examines and contrasts the potential ethical implications of memory modification treatment via implantable neurotechnologies. The study contends that undesired side effects resulting from memory modulation can lead to significant identity harms, disrupting the coherence of self-narratives and impinging on our authenticity. To evince the practical impact of this moral argument, the study conducts a practical ethical assessment of how employing implantable neurotechnologies to modulate memory may jeopardize (i) our moral responsiveness to events and core system of values and (ii) the emotional component associated with the altered memory. From a first-person standpoint, changes to the way we reasonably feel and react to past events and future intentions may be deemed ethically problematic as these profound changes can yield significant moral disruptions and negatively impact our personal lives and interpersonal relationships. In addition, the study discusses further ethical conundrums from a third-person perspective as these disruptions can inhibit social activism against structural injustices, thereby hindering societal progress. Thus, taking into account this societal dimension is paramount when evaluating the ethical permissibility of memory modification procedures.